Improving Tracking Efficiency of Two-Axis Sun Tracking Systems - (:unkn) unknown (SPRINGER INTERNATIONAL PUBLISHING AG, 2017)
Due to both reduction and insufficient of fossil fuel to supply current growing energy needs, investigation and employing of renewable resources has been accelerated. Besides, using fossil fuel affected the environment negatively. Therefore, renewable energy resources in the most studies are solar, wind and geothermal. In this study, electrical energy production methods from solar energy have been examined, a fixed and a two axis tracking system have been designed. Both systems are compared each other regarding to several factors by performing annual measurements. Energy consumption of the system is minimized by employing actuator motor in two axis solar tracking system. According to the efficiency of two-axis tracking system, the annual average has been calculated as 31.67% more. This efficiency has been calculated as 70% in winter, 11% in summer. As a result of these measurements several graphics of a year empirically daily, monthly and annual data have been contributed to the literature for Diyarbakir, one of the prominent cities of Southern east, having the most solar energy of Turkey. In the first section, literature review will be indicated. In the second section, solar angles, photovoltaic panels and systems, sample designs and solar tracking systems are examined. In the third section, photovoltaic two-axis solar tracking system and qualifications, work and advantages of fixed system which we designed are stated. In following section, obtained results will be given and in last section, financial analysis of fixed and tracking photovoltaic systems has been performed. Also, recommendations for increasing their efficiency have been noted.
Keywords: Solar energy; Photovoltaic; Two-axis sun tracking; OUTPUT